Improvements in mass-rearing of the Philippines fruit fly Bactrocera philippinensis (Diptera: Tephritidae). (4th September 2014) - Resilva, Sotero S.; Obra, Glenda B.
Abstract : In this study, new methods to improve the mass production of the Philippines fruit fly Bactrocera philippinensis Drew & Hancock were assessed. A new adult screen cage equipped with perforated egging tubes was designed. The replacement of sweet potato with sugarcane bagasse, rice straw or powdered corn as an alternative bulking agent in the standard artificial larval diet was found to lead to positive results in large-scale rearing. Rearing protocols and product quality control procedures for egg incubation, sieving of pupae and pupal holding were examined. The adoption of these new rearing procedures at low cost was found to increase the production of the Philippines fruit fly in a mass-rearing facility without reducing the fitness of the insect.